MULTITEMPORAL ANALYSIS OF DYNAMICS OF COVER AND LAND USE IN THE CAÇAPAVA DO SUL CITY – RS THROUGH LANDSAT IMAGES - Nunes, Matheus Mesquita da Costa; Lippert, Diogo Belmonte; Silva, Caroline Kist da; Pereira, Rudiney Soares; Marchesan, Juliana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This study aims to analyze the evolution of the use and land cover and forest dynamics mainly in the city of Caçapava do Sul in the period 1991-2011. Held digital supervised classification using the maximum likelihood algorithm. The thematic classes were chosen: Planted Forest, Native Forest, Field, Bare Soil, Water and Crops of Winter. Analyzing the classes within these years, we can say that there has been significant change in the class Planted Forest which increased by over 50% in 2011 compared to 1991, however, its area does not correspond to 1% of the municipality. The class with the highest expansion was the Bare Soil, for the period 1991-2011 grew 117.40 km² 58% in the period 1991 to 2011. Classes Native Forest and Field, have coverage of 90% and other uses, distributed in the remaining 10% of the municipal area.